(untitled) (BIRDEM Medical Journal, 2025)
Background: Patients with end-stage renal disease (ESRD) require dialysis for their survival. Haemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) are two different modes of dialysis which can lead to multitude of stressful physical, mental and social problems. This study was done to evaluate the health related quality of life (HRQOL) of ESRD patients undergoing HD and CAPD. Methods: This cross-sectional analytical study was conducted in the Department of Nephrology, BIRDEM General Hospital, Dhaka during January 2019 to June 2020. A total of 66 ESRD patients undergoing HD or CAPD were taken after obtaining informed written consent. Information on socio-demographic characteristics, clinical features and laboratory investigations were assessed. HRQOL was assessed by using the validated Bengali version of Kidney Disease Quality of Life Short Form Tool (KDQOL-SF-36 version1.3). A semistructured questionnaire was used for data collection and analysis was done by Statistical Package for Social Science (SPSS) version 24.0. Results: Majority of ESRD patients underwent HD (54.5%). Age was significantly associated with dialysis treatment modality (HD vs CAPD: 55.6±11.9 vs 62.9±11.9 years, p<0.05). According to SF-36 and KDQOLSF 1.3 assessment, patient undergoing CAPD had a better QOL and mental health compared to HD. Among SF- 36 domain, physical functioning had a significant positive relation with haemoglobin level (r=0.320, p=0.009). Haemoglobin level was positively correlated with symptoms, effects of kidney disease and burden of kidney disease in KDQOL-SF 1.3 scores (p<0.05). Conclusion: CAPD patients demonstrated a better QOL compared to HD patients. BIRDEM Med J 2025; 15(1): 9-15